Unusual Case of Localized Upper Limbs and Truncal Edema Associated with Fever, Anemia, and Acute Kidney Injury - Mohammad Tinawi (Case Reports in Medicine)
The patient is a 75-year-old man who presented with right arm pain, edema, and erythema. The same manifestations appeared in the other arm 3 weeks later. He also developed fever, acute kidney injury, anemia, and truncal edema. Initial extensive evaluation was unrevealing. He was noted to have elevated creatine kinase, and a diagnostic muscle biopsy lead to diagnosis of inflammatory myositis. He improved with corticosteroids.